Implant stability of narrow diameter implants in hyperglycemic patients—A 3‐month case–control study - Daniel Diehl; Marianna Winkler; Hakan Bilhan; Anton Friedmann (Clinical and Experimental Dental Research, 2022)
Abstract Objectives The aim of this prospective case–control study was to compare the development of implant stability quotients of narrow diameter implants in patients with type 2 diabetes mellitus (T2DM) and healthy individuals within the first 3 months after implant insertion. Methods Sixteen patients with T2DM (HbA1C > 6.5%) as test group and 16 nondiabetic patients (HbA1C < 5.9%) as the control group were evaluated. All patients received narrow‐diameter tissue level implants in an edentulous area posterior to the canine. The implant stability was measured by means of resonance frequency analysis after 3 days, 7 days, 4 weeks, and 3 months postplacement. Statistical analysis of intergroup differences and correlation to HbA1c values and treated jaw was performed in PRISM 8. Results The means for implant stability quotients showed a significant increase between Day 3 and 3‐month assessment in both groups. No significant differences between study groups and no correlation of implant stability to HbA1c were found. Conclusion The present study shows encouraging clinical outcomes for narrow‐diameter implants inserted in the posterior zone in patients with uncontrolled T2DM.